LINGUISTIC TAGGING AND IDEOLOGY IN SELECTED ENGLISH-MEDIUM NIGERIAN AND CAMEROONIAN NEWSPAPER REPORTS ON THE BAKASSI PENINSULA BORDER CONFLICT (2013)
Linguistic tagging, the labelling of people and their actions with particular socio-politically-grounded values, is an ideological denominator that plays a significant role in media framing of conflict. Despite this significance, existing studies on the Nigeria-Cameroon Bakassi Peninsula border conflict, which had concentrated on the historical, political, legal and sociolinguistic dimensions, largely neglected an exploration of the dynamics of linguistic tagging. Therefore, this study investigated the linguistic tagging of people and their actions, and the underlying social, political and economic ideologies in the Nigerian and Cameroonian newspaper reports on the Bakassi Peninsula border conflict, with a view to uncovering the interactions between the tagging and the ideologies. The theoretical framework was a synthesis of insights from van Dijk’s socio-cognitive model of Critical Discourse Analysis, Halliday’s Systemic Linguistics and the theory of lexical decomposition. Data were collected from three Nigerian newspapers (The Guardian, The Punch and The Nigerian Chronicle) and three Cameroonian newspapers (The Cameroon Tribune, The Post and Eden), published in English between August 2006 and August 2010. These newspapers were purposively selected on the basis of their wide virtual and non-virtual publicity on the conflict. Out of a total of 650 news reports, 164 (87 Nigerian and 77 Cameroonian news reports) were purposively selected and subjected to content, linguistic and descriptive statistical analyses. Five conflict-related themes, namely, terrorism, resistance, dispossession, suffering and economy, which correlated with different forms of linguistic tagging, were identified. Terrorism took lexical tags of violence, and resistance, the tags of militancy. Dispossession and suffering took the tags of dislocation, and economy, the tags of ownership. These tags featured emotive and evaluative adjectives and intensifying adverbs. The themes of terrorism and resistance were tagged by transitive clauses of action, while dispossession and suffering were represented by metaphors UNIVERSITY OF IBADAN LIBRARY xv and verbs signifying mental conditions. Economic interests in the Peninsula were represented positively while violence, militancy and dislocation evoked negative connotations. Ostensibly to attract international support, Cameroonian newspaper reports emphasised tags of violence (46.0%), militancy (37.0%), ownership (14.0%) and dislocation (3.0%) while the Nigerian ones devoted more attention to tags of dislocation (53.0%), ownership (36.0%), militancy (9.0%) and violence (2.0%). Ideologically, the tags were motivated by specific values. The economic value of consumerism motivated the tagging of ownership in both nations’ newspapers. However, in the Nigerian reports, the values of social justice and altruism mediated the tagging of dislocation while in the Cameroonian reports, the political ideals of pacifism and patriotism triggered violence and militancy tags. Cameroonian reports had a larger concentration of agentless passives (76.0%) than Nigerian ones (24.0%) to obscure media bias. Nominalisations were deployed in the Nigerian reports (54.0%) and the Cameroonian ones (46.0%) to play down media involvement. There is a dynamic interaction between socio-political and economic ideologies and linguistic tagging in the newspaper reports on the Bakassi Peninsula border conflict. This interaction projected respectively social concerns and political rights and peace in Nigerian and Cameroonian reports. Thus, an awareness of this interaction is essential to the understanding of media reports on border conflicts. Key words: Linguistic tagging, Newspaper reports, Ideology, Bakassi Peninsula conflict Word count: 498